Are Cash Transfers Effective at Empowering Mothers? A Structural Evaluation of Mexico’s Oportunidades - Flores, Andrea (The Review of Economics and Statistics, 2026)
Abstract This paper exploits the exogenous variation of Mexico’s Oportunidades conditional cash transfer program on urban households’ time and consumption allocations to identify and structurally estimate a collective labor supply model with home production. I use my structural estimates to show that participation in Oportunidades increased maternal intrahousehold bargaining power by almost 13%, which is associated with an increase of approximately 14% in the production of a child-related public good in dual-earner beneficiary households. Counterfactual exercises show that Oportunidades is as effective as alternative cash transfer programs and wage subsidies at increasing mothers’ bargaining power, control over household monetary resources, and domestic output.